The Wolves of Mercy Falls: Sinner - Book 4 - Stiefvater, Maggie 1981- (New York : Scholastic Press, 2014)
Cole St. Clair has come to California for one reason: to get back Isabel Culpeper.
Keywords: Metamorphosis -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Wolves -- Juvenile fiction; Paranormal fiction; Supernatural -- Fiction; Metamorphosis -- Fiction; Human-animal relationships -- Fiction; Wolves -- Fiction; California -- Juvenile fiction; California -- Fiction